Yahp!: Yet Another Haptic Probe - Tau, Martín Ezequiel (2026)
Characterizing the relationship between vibratory stimuli and user responses is a complex challenge due to varying skin sensitivity across body areas and the onset of stimulus saturation. Achieving an optimal balance between body location, actuator types, and haptic cues is often a demanding and error-prone process. This paper presents Yahp! (Yet Another Haptic Probe), an open-source tool developed through a collaboration between the National University of La Plata and Stream S.A. to systematically design and execute user perception tests for industrial haptic alerts. Yahp! facilitates the evaluation of actuator settings and body locations through a modular architecture consisting of formal experiment definitions, a results database, a mobile trial director, and a generic haptic device utilizing a low-level messaging protocol. To demonstrate the tool’s utility, we present two experiments focusing on haptic bracelets and sleeves. Our preliminary results indicate that while 10% vibration intensity is consistently below the detection threshold, higher intensities are reliably perceived within an average of 3.5 seconds. Furthermore, the studies revealed significant detectability asymmetries during intensity transitions and confirmed the impact of sensory saturation on cue recognition. These findings suggest that Yahp! is an effective platform for defining the symbolic language of haptic interfaces in real-world applications.